2019
DOI: 10.1101/732594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Null results from a dimensional study of error-related negativity (ERN) and self-reported psychiatric symptoms

Abstract: Alterations in error processing are implicated in a range of DSM-defined psychiatric disorders. For instance, obsessive-compulsive disorder (OCD) and generalised anxiety disorder show enhanced electrophysiological responses to errors -i.e. errorrelated negativity (ERN) -while others like schizophrenia have an attenuated ERN.However, as diagnostic categories in psychiatry are heterogeneous and also highly intercorrelated, the precise mapping of ERN enhancements and impairments is unclear. To address this, we re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…During the in-person EEG session, participants completed two tasks: the modified Eriksen flanker task (Eriksen & Eriksen, 1974) and the two-step reinforcement learning task (Daw et al, 2011(Daw et al, , 2005. Data from the former task data are presented elsewhere (Seow et al, 2019), but note that we also reported the basic association with compulsivity and model-based planning in that paper, which served to contextualise a null result. Once participants had completed both tasks, they completed a short IQ evaluation before debriefing.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…During the in-person EEG session, participants completed two tasks: the modified Eriksen flanker task (Eriksen & Eriksen, 1974) and the two-step reinforcement learning task (Daw et al, 2011(Daw et al, , 2005. Data from the former task data are presented elsewhere (Seow et al, 2019), but note that we also reported the basic association with compulsivity and model-based planning in that paper, which served to contextualise a null result. Once participants had completed both tasks, they completed a short IQ evaluation before debriefing.…”
Section: Methodsmentioning
confidence: 84%
“…The effect size indicated that N = 150 participants were required to achieve 90% power at 0.05 significance. Our final sample was larger than this to achieve the required power for another study that the same subjects participated in (Seow et al, 2019). Procedure.…”
Section: Methodsmentioning
confidence: 99%